2017
DOI: 10.1128/jcm.00818-17
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Diagnostics Update for the Emerging (If Not Already Widespread) Sexually Transmitted Infection Agent Mycoplasma genitalium: Just About Ready for Prime Time

Abstract: Mycoplasma genitalium is an important and emerging agent of sexually transmitted infection in females and males, carrying the potential for postinfection genital tract sequelae. Past efforts to identify this organism on a routine basis, which were problematic due to the fastidious nature of the bacterium and its antigenic intricacies, have recently become supplemented by molecular diagnostics. A number of these assays are available commercially. This minireview describes the format and performance indices of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Our results support the argument for close monitoring of antibiotic resistance in M. genitalium in Singapore, as in the rest of the world. Management of such resistance relies on timely diagnosis and appropriate treatment, ideally with subsequent confirmation of clearance of M. genitalium infections, but although diagnosis of M. genitalium has never been easier in light of novel and more convenient molecular tests [4], M. genitalium is often not part of routine screening or tested for in cases of NGU [8,30]. Evidently the ideal approach would be to consider M. genitalium in all cases of NGU, routine screening and monitoring of populations at risk of high M. genitalium transmission, and susceptibility-guided therapy of treatment failures [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results support the argument for close monitoring of antibiotic resistance in M. genitalium in Singapore, as in the rest of the world. Management of such resistance relies on timely diagnosis and appropriate treatment, ideally with subsequent confirmation of clearance of M. genitalium infections, but although diagnosis of M. genitalium has never been easier in light of novel and more convenient molecular tests [4], M. genitalium is often not part of routine screening or tested for in cases of NGU [8,30]. Evidently the ideal approach would be to consider M. genitalium in all cases of NGU, routine screening and monitoring of populations at risk of high M. genitalium transmission, and susceptibility-guided therapy of treatment failures [31].…”
Section: Discussionmentioning
confidence: 99%
“…Mycoplasma genitalium is a sexually transmitted pathogen of rapidly increasing significance [1], which may cause cervicitis and urethritis in women and has been linked to pelvic inflammatory disease and infertility [2], as well as with non-gonococcal urethritis (NGU) in men [3]. Diagnosis of M. genitalium by bacterial culture is difficult due to requirements for specific media and prolonged incubation; in practice, diagnosis is constrained by a necessary reliance on molecular methods [4].…”
Section: Introductionmentioning
confidence: 99%
“…genitalium has been recently recognized as an important pathogen implicated in pelvic inflammatory disease and infertility [12,78]. Although some early diagnostic tests have been described [79,80], very few clinicians test for its presence. Furthermore, the vaginal microbiota composition has been reported to be associated with the progression of HPV infection, from early states to cervical cancer [37,40].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have identified a link between M. genitalium and increased HIV acquisition (30,31). Although this organism was first characterized as a pathogen in the 1980s, recognition of M. genitalium as a significant cause of urethritis has been hampered by the lack of reliable diagnostic methods (32). Because of fastidious growth requirements and an extremely slow growth rate, culture is not practical for diagnosis (33), and serologic testing is of limited value because of antigenic variation in M. genitalium and cross-reactivity (34,35).…”
Section: Stismentioning
confidence: 99%